Predictors of postpartum depression service use: A theory-informed, integrative systematic review - Bina, Rena (Women and birth : journal of the Australian College of Midwives, 2020)
Postpartum depression affects many women globally, yet rates of treatment use are low. A comprehensive view of factors associated with treatment use, from women’s and providers’ perspectives, based on a theoretical model is lacking. Several studies examined various factors associated with postpartum depression service use; however, each study focused on a small number of factors. This study describes a systematic literature review based on the Behavioral Model of Health Service Use. The purpose of this article is to review and synthesize the available literature regarding factors associated with women’s mental health service use for postpartum depression from women’s and healthcare providers’ perspectives, and provide a comprehensive integrative view of the subject. Three electronic databases were searched, and 35 studies published up to 2018 in English language journals met inclusion criteria for review. Factors associated with postpartum depression service use were classified according to the Behavioral Model of Health Service Use’s constructs. Service use for postpartum depression is a function of a woman’s predisposition to use mental health services; individual, familial, and communal factors which enable or pose barriers to use of mental health services; and the woman’s perceived or evaluated need for treatment. In addition, societal determinants impact the woman’s decision to seek help directly or through impacting the health and mental health care service system’s resources and organization. This review illustrates key factors for researchers and practitioners to consider when treating postpartum women and developing interventions to enhance postpartum depression treatment use.